New insights on the wooden weapons from the Paleolithic site of Schöningen. Issue 89 (December 2015) - Schoch, Werner H.; Bigga, Gerlinde; Böhner, Utz; Richter, Pascale; Terberger, Thomas
Abstract: The Paleolithic site of Schöningen is famous for the earliest known, completely preserved wooden weapons. Here we present recent results of an ongoing analysis of the nine spears, one lance, a double pointed stick, and a burnt stick dating to the Holsteinian, c. 300 kyr. Macroscopic and microscopic analyses, as well as studies of thin sections, contribute to a better understanding of the manufacture of the wooden weapons. They were deposited in organic sediments at a former lakeshore among numerous bones of butchered horses. In general, the spears are extremely well-preserved and show no or little sign of taphonomic alteration, although some of the weapons are broken and parts were slightly moved, probably by water action. The excellent preservation conditions provide considerable information on the operational sequence of production. The hunters selected thin trunks of spruce or pine and initially stripped off the bark. Traces of cutting, scraping, and smoothing can be observed on the spear surfaces in detail. In the case of spear X, repeated use of the weapon is implied by re-sharpening of the tip. Analyses of wood anatomy provide information on climatic conditions and contribute to the better understanding of the development of the site.